Rights of Indians and tribes - Pevar, Stephen L. (New York, USA: Oxford University Press, 2022)
"MILLIONS OF PEOPLE AND HUNDREDS OF nations inhabited what is now the continental United States when Europeans first arrived in North America. The Indigenous peoples, known today as Indians, American Indians, or Native Americans, lived in communities spread across the land. Most lived along the coasts, the major rivers, and the Great Lakes, as people in the United States do now. Each nation possessed its own government, culture, and language. Nearly seven million Indians reside in the United States today, about two percent of the nation's population. Most Indians live west of the Mississippi River, but ten percent live in the Northeast. The states with the highest number of Indians are California, Oklahoma, Arizona, Texas, New York, New Mexico, Washington, North Carolina, Florida, and Michigan, in that or-der. The states in the continental United States with the highest percentage of Indigenous peo-ples are Alaska (nearly 15 percent), Oklahoma (nearly 13 percent), and New Mexico (nearly 11 percent)"--
Map : the federal and the state recognized tribes -- A history of Federal Indian Policy -- Definitions : Indian, Indian Tribe, Indian Country, and Indian Title -- The trust responsibility -- Indian Treaties -- Federal power over Indian affairs -- Tribal self-government -- Criminal jurisdiction in Indian Country -- Civil jurisdiction in Indian Country -- Taxation -- Indian Hunting and Fishing Rights -- Indian Water Rights -- Civil Rights of Indians -- The Indian Civil Rights Act -- The unique status of certain Indian Groups -- Indian gaming -- The Indian Child Welfare Act -- Judical review.
Includes bibliographical references and index.
Keywords: Indians of North America -- Legal status, laws, etc; Sociology; Indian country (United States law); Tribal government -- Law and legislation -- United States; Federal-Indian trust relationship